Implementasi Sistem Informasi Tangkapan Nelayan dan Pemasaran (SITANPAS) di Desa Ambesia Selatan - Rahman, Yuli Asmi; Anwar, Khairil; Din, Muhammad; Mardjudo, Ahsan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
The fishing community in South Ambesia Village faces major obstacles, including limited market access and a long catch distribution chain. To address these issues, an innovative information technology application, the SITANPAS (Fisherman's Catch Information and Marketing System), has been implemented, integrated with ICT devices on fishing nets and catch monitoring posts at the docks. This initiative began with outreach, training, and assistance in using the application, followed by the installation of catch monitoring devices and the strengthening of the fishermen's cooperative as a platform for business management and product distribution. The implementation results demonstrate increased marketing efficiency, with fishermen able to report their catches in real time, and buyers gaining direct access to seafood at more competitive prices. Sales lead times are reduced, distribution is faster, and market reach is expanded. Furthermore, the cooperative strengthens financial and marketing governance, giving fishermen a better bargaining position. Scientific findings from this initiative confirm that the digitalization of coastal community-based information systems can drive the transformation of fishing villages toward sustainable economic independence.